Spina ventosa with lupus vulgaris and lymphadenopathy: Multifocal tuberculosis - Sanjeev Sharma; Shikha Sood; Mudita Gupta (Wolters Kluwer Medknow Publications, 2015)
Tuberculous dactylitis is a rare yet well-recognized disease of small bones of the hands and feet. It occurs in young children below five years of age. Tubercular dactylitis with lupus vulgaris and lymphadenopathy was suspected clinically and radiologically in an 8-year-old girl who had multiple soft tissue swelling of hands and feet with ulceration, encrustations, and an atrophic scar with lytic expansile lesions of the small bones of the hands and feet. Tubercular lymph node involvement was confirmed histopathologically.